2018
DOI: 10.1021/acsomega.8b01893
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Purification, and Mass Spectrometric Characterization of Stable Isotope-Labeled Amadori-Glycated Phospholipids

Abstract: Nonenzymatic glycation of lipids plays an important role in several physiological and pathological processes, such as normal aging and complications of diabetes mellitus. To develop liquid chromatography coupled with mass spectrometric (LC-MS) methods for accurate analysis of Amadori compound-glycated lipids from biological samples, it is essential to obtain isotope-labeled Amadori-lipid standards. Herein, we report optimized methods for the preparation of six stable isotope-labeled Amadori-glycated lipid stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…First, LC-NLS-MS was performed to scan precursor ions, which had neutral loss of 303 Da in positive mode and 162 Da in negative mode. These two neutral loss are characteristic of Amadori-PE/LPE as reported previously. , LC-NLS-MS in positive and negative modes led to two lists of possible Amadori-PE/LysoPE species. Species shared by the two lists were defined as candidate Amadori-PE/LysoPE species.…”
Section: Results and Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…First, LC-NLS-MS was performed to scan precursor ions, which had neutral loss of 303 Da in positive mode and 162 Da in negative mode. These two neutral loss are characteristic of Amadori-PE/LPE as reported previously. , LC-NLS-MS in positive and negative modes led to two lists of possible Amadori-PE/LysoPE species. Species shared by the two lists were defined as candidate Amadori-PE/LysoPE species.…”
Section: Results and Discussionsupporting
confidence: 83%
“…Okudaira et al used acidic MeOH (pH 4.0) to extract lysophospholipids from mouse plasma, serum, and tissues, and their work showed that the relatively lower pH could help to inhibit the migration of acyl chain in lysophospholipids from sn -2 to sn -1 position . Alternatively, we used phenyl boronate affinity (PBA) resin to separate Amadori-PE from PE during synthesis of Amadori-PE standards …”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations